The Effect of Facial Massage on Mouth Closure Ability in Toddlers at Pal 3 Community Health Center, Pontianak - Therecia Wijayati; Marice Marice; Youlenta Ernesotha (Open Access Health Scientific Journal, 2026)
Background: Feeding difficulties associated with poor mouth closure ability may impair oral motor function and negatively affect nutritional intake and child growth. Facial massage has been introduced as a simple, non-pharmacological intervention to stimulate facial muscles and improve oral motor performance; however, evidence regarding its effectiveness among toddlers remains limited. This study aimed to determine the effect of facial massage on mouth closure ability among toddlers at Pal 3 Community Health Center, Pontianak.Methods: A quantitative pre-experimental study with a one-group pretest–posttest design was conducted from January to March 2026 at Pal 3 Community Health Center, Pontianak. A total of 40 toddlers aged 1–5 years were recruited using purposive sampling. Facial massage using almond oil was administered twice weekly. Mouth closure ability was assessed before and after the intervention using a structured observation checklist. Data were analyzed using descriptive statistics and inferential analysis, with statistical significance set at p < 0.05.Results: Before the intervention, 90.0% of toddlers demonstrated poor mouth closure ability, while only 10.0% showed good mouth closure ability. Following facial massage, the proportion of toddlers with good mouth closure ability increased to 90.0%, whereas the proportion with poor mouth closure ability decreased to 10.0%. The mean mouth closure score increased from 2.25 ± 2.34 to 7.20 ± 2.80, with a mean difference of 4.95 ± 0.47. Statistical analysis revealed a significant improvement after the intervention (p < 0.001).Conclusion: Facial massage significantly improved mouth closure ability among toddlers and may serve as a safe, simple, and cost-effective complementary intervention to enhance oral motor function in primary healthcare settings.